Awareness and impact of educational intervention regarding kangaroo mother care among pediatricians of Marathwada region of Maharashtra - Tiwari, Manish; Pise, Harshal N (Indian Journal of Child Health, 2018)
Objective: The objective of the study was to compare knowledge and attitudes toward kangaroo mother care (KMC) among pediatric practitioners in Marathwada region before and after a workshop on KMC. Material and Methods: A prospective comparative study was conducted among 40 pediatricians practising in the rural area of Marathwada region. Clinicians having at least Level 2 neonatal intensive care unit setup at their place were enrolled in the study. Every pediatrician satisfying the selection criteria and willing to participate was enrolled in the study. They were given a questionnaire, consisting 25 questions, which were supposed to be answered at the time of enrolment, i.e., pre-test. After that, the participant was given a short booklet on KMC to read, and then after a gap of 7 days, the participant attended a workshop on KMC for 4 h, in which details regarding KMC, advantages of KMC, and videos showing actual practice of KMC were shown to participants. After completion of workshop, participants were given the same questionnaire and pre- and post-test scores were calculated. Results: The mean score in basic knowledge was 20